Electrical and Photoresponse Properties of p-CuGaO2-on-p-Si/Al Photodiode - Elsayed, I. A.; Fahmy, T.; El-Tantawy, Farid; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
We synthesized CuGaO2 film by sol gel method to prepare a photodiode of p-Si/CuGaO2. The structural properties of the CuGaO2 film were investigated using atomic force microscope (AFM). The optical band gap of the CuGaO2 film was found to be 3.64 eV. The photoresponse characteristics indicate that the diode exhibits a photoconducting behavior. The photosensitivity value under 100 rriW/cm(2) was found to be of 6.80 x 10(2). The ideality factor and barrier height of the diode were obtained to be 2.02 +/- 0.06 and 0.60 +/- 0.4 eV, respectively. The interface states of the diode were determined by conductance technique and was found to be similar to 10(15) eV(-1)cm(-1). It is evaluated that p-CuGaO2-on-p-Si/Al photodiode can be used for optoelectronics applications.
Keywords: CuGaO2 Film; Photodiode; Sol-Gel